Josef Svejk in the situation of modern novel - Kubicek, Tomas (Bohemica Olomucensia, 2013)
The paper deals with Hasek's text as the ingenious game with paradoxes. Paradox is reflected here as the compositional and thematical strategy in its formal and ideological aspects. The author describes the Hasek's fictional world not as absurd, but only as world denying the logics that approaches the man as the object only. Svejk as the person is a formulation of conviction that people can preserve their destiny in their own hands face to face with the ruthless mechanism of history.